In search of ideas: Technological innovation and executive pay inequality - Frydman, Carola; Papanikolaou, Dimitris (Journal of Financial Economics, 2018)
We develop a general equilibrium model that delivers realistic fluctuations in pay inequality as a result of changes in the technology frontier. In our model, executives add value to the firm not only by participating in production decisions, as do other workers in the economy, but also by identifying new investment opportunities. Improvements in technology that are specific to new vintages of capital raise the return to managers’ skills for discovering new growth projects and, thus, increase the compensation of executives relative to workers and disparities in pay across executives. Our model implies that, controlling for firm size, compensation is higher in fast-growing firms and that pay inequality increases as investment opportunities in the economy improve. Both predictions are consistent with the data.